PENGARUH ENVIRONMENTAL, SOCIAL DAN GOVERNANCE DISCLOSURE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Sari Rahma Dhani; Neneng Salmiah; Fahmi Oemar (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the effect of environmental, social, and governance (ESG) disclosure on the firm value of energy sector companies listed on the Indonesia Stock Exchange (IDX). The population of this study consists of all energy sector companies listed on the IDX, totaling 91 companies. The sample was selected using a purposive sampling method, namely selecting samples based on predetermined criteria. As a result, the final sample comprises 33 energy sector companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study is multiple regression analysis. The results show that simultaneously, environmental, social, and governance disclosure have an effect on firm value. Partially, environmental disclosure has no effect on firm value, while social disclosure has a negative and significant effect on firm value, and governance disclosure has a positive and significant effect on firm value. The Adjusted R-squared value is 0.249 or 24.9%, indicating that environmental, social, and governance disclosure contributes 24.9% to firm value, while the remaining 75.1% is influenced by other variables not examined in this study.